Unprecedented nucleophile-promoted 1,7-S or Se shift reactions under Pummerer reaction conditions of 4-alkenyl-3-sulfinylmethylpyrroles - Go, Takashi; Morimatsu, Akane; Wasada, Hiroaki; Tanabe, Genzoh; Muraoka, Osamu; Sawada, Yoshiharu; Yoshimatsu, Mitsuhiro (Beilstein Journal of Organic Chemistry, 2018)
A unique 1,7-S- and Se-shift reaction under Pummerer reaction conditions of 4-alkenyl-3-sulfinyl- and seleninylpyrroles was described. The usual Pummerer reaction of 4-(alkenylaminomethyl)-3-phenylsulfinylpyrroles and a successive reaction with tetrabutylammonium hydroxide (TBAH) yielded either pyrrolo[3,2-c]azepines or N-pyrrol-3-ylmethyl-N-(4-hydroxy-3-sulfanylpropyl)-p-toluenesulfonamides (diols). Seleno-Pummerer reactions of 3-selanylmethylpyrroles also proceeded via in situ generation of selenoxides, followed by a treatment with TBAH.
Keywords: hydroamination; Pummerer reaction; pyrrole; pyrroloazepine; 1,7-sulfur shift

Inhibitors of Cyclin-dependent Kinases as Anti-tumor Agents - Kunick, C.; Lemcke, T.; Meijer, L. (Development, Selectivity, and Application of Paullones, a Family of CDK Inhibitors, 2006)

(untitled) - Gussio, R.; Zaharevitz, D. W.; McGrath, C. F.; Pattabiraman, N.; Kellog, G. E.; Schultz, C.; Link, A.; Kunick, C.; Leost, M.; Meijer, L.; Sausville, E. A. (Anti-Cancer Drug Des., 2000)

(untitled) - Forte, B.; Malgesini, B.; Piutti, C.; Quartieri, F.; Scolaro, A.; Papeo, G. (Mar. Drugs, 2009)

(untitled) - Nguyen, T. N. T.; Tepe, J. J. (Curr. Med. Chem., 2009)

(untitled) - Linington, R. G.; Williams, D. E.; Tahir, A.; van Soest, R.; Andersen, R. J. (Org. Lett., 2003)

(untitled) - Schultz, C.; Link, A.; Leost, M.; Zaharevitz, D. W.; Gussio, R.; Sausville, E. A.; Meijer, L.; Kunick, C. (J. Med. Chem., 1999)

(untitled) - Tolle, N.; Kunick, C. (Curr. Top. Med. Chem., 2011)

(untitled) - Bridges, A. J. (Chem. Rev., 2001)

(untitled) - Brault, L.; Migianu, E.; Neguesque, A.; Battaglia, E.; Bagrel, D.; Kirsch, G. (Eur. J. Med. Chem., 2005)

(untitled) - Tang, P. C.; Su, Y. D.; Feng, J.; Fu, J. H.; Yang, J. L.; Xiao, L.; Peng, J. H.; Li, Y. L.; Zhang, L.; Hu, B.; Zhou, Y.; Li, F. Q.; et al. (J. Med. Chem., 2010)

(untitled) - Meijer, L.; Thunnissen, A.-M.; White, A. W.; Garnier, M.; Nikolic, M.; Tsai, L.-H.; Walter, J.; Cleverley, K. E.; Salinas, P. C.; Wu, Y. Z.; Biernat, J.; Mandelkow, E.-M.; et al. (Chem. Biol., 2000)

(untitled) - Albrecht, B. K.; Gehling, V. S.; Hewitt, M. C.; Vaswani, R. G.; Côté, A.; Leblanc, Y.; Nasveschuk, C. G.; Bellon, S.; Bergeron, L.; Campbell, R.; Cantone, N.; Cooper, M. R.; et al. (J. Med. Chem., 2016)

(untitled) - Kumar, A.; Vachhani, D. D.; Modha, S. G.; Sharma, S. K.; Parmar, V. S.; Van der Eycken, E. V. (Eur. J. Org. Chem., 2013)

(untitled) - Haibach, M. C.; Deb, I.; De, C. K.; Seidel, D. (J. Am. Chem. Soc., 2011)

(untitled) - Modha, S. G.; Kumar, A.; Vachhani, D. D.; Sharma, S. K.; Parmar, V. S.; Van der Eycken, E. V. (Chem. Commun., 2012)

(untitled) - Yokosaka, T.; Nemoto, T.; Hamada, Y. (Chem. Commun., 2012)

(untitled) - Zhu, W.; Zhao, L.; Wang, M.-X. (J. Org. Chem., 2015)

(untitled) - Garcia, S.; Schulz, J.; Pellet-Rostaing, S.; Lemaire, M. (Synlett, 2008)

(untitled) - Feng, J.-J.; Lin, T.-Y.; Wu, H.-H.; Zhang, J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Feng, J.-J.; Lin, T.-Y.; Wu, H.-H.; Zhang, J. (J. Am. Chem. Soc., 2015)

(untitled) - Martı́nez, L. R.; Gustavo Avila Zarraga, J.; Duran, M. E.; Ramı́rez Apam, M. T.; Cañas, R. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Mizuno, A.; Ogata, A.; Kamei, T.; Shibata, M.; Shimamoto, T.; Hayashi, Y.; Nakanishi, K.; Takiguchi, C.; Oka, N.; Inomata, N. (Chem. Pharm. Bull., 2000)

(untitled) - Li, X.; Chen, D.; Gu, H.; Lin, X. (Chem. Commun., 2014)

(untitled) - Grigg, R.; Sridharan, V.; Sykes, D. A. (Tetrahedron, 2008)

(untitled) - Shi, Z.; Ren, Y.; Li, B.; Lu, S.; Zhang, W. (Chem. Commun., 2010)

(untitled) - Sharma, S. K.; Sharma, S.; Agarwal, P. K.; Kundu, B. (Eur. J. Org. Chem., 2009)

(untitled) - Beaumont, S.; Retailleau, P.; Dauban, P.; Dodd, R. H. (Eur. J. Org. Chem., 2008)

(untitled) - Bennasar, M.-L.; Roca, T.; García-Díaz, D. (J. Org. Chem., 2007)

(untitled) - Nyerges, M.; Pintér, Á.; Virányi, A.; Bitter, I.; Tőke, L. (Tetrahedron Lett., 2005)

(untitled) - Ferrer, C.; Echavarren, A. M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Gruit, M.; Michalik, D.; Tillack, A.; Beller, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Nagata, H.; Sugimoto, Y.; Ito, Y.; Tanaka, M.; Yoshimatsu, M. (Tetrahedron, 2014)

(untitled) - Kobayashi, Y.; Tanahashi, R.; Yamaguchi, Y.; Hatae, N.; Kobayashi, M.; Ueno, Y.; Yoshimatsu, M. (J. Org. Chem., 2017)

Comprehensive Organic Synthesis - Kennedy, M.; McKervey, M. A. (Oxidation adjacent to Sulfur, 1991)

Sulfur-Mediated Rearrangements I - Akai, S.; Kita, Y. (Recent Advances in Pummerer Reactions, 2006)